Can Social Media Inform Corporate Decisions? Evidence from Merger Withdrawals - COOKSON, J. ANTHONY; NIESSNER, MARINA; SCHILLER, CHRISTOPH (Journal of Finance, 2026)
ABSTRACT This paper studies whether social media sentiment predicts merger withdrawals. We find that a one‐standard‐deviation increase in social media sentiment after a merger announcement is associated with a 0.64 percentage point lower probability of withdrawal (16.6% of the average). This effect is unexplained by abnormal price reactions, traditional news, and analyst recommendations. Consistent with manager learning, the informativeness of social media strengthens after firms start corporate Twitter accounts. The informativeness is driven by longer acquisition‐related tweets by fundamental investors, rather than memes and price trend tweets. These findings suggest that social media signals can be important for corporate decisions.